2022
DOI: 10.3390/diseases10030037
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin: A Molecule of Great Biochemical and Clinical Value and Its Beneficial Effect on Diabetes and Cancer

Abstract: Quercetin belongs to the broader category of polyphenols. It is found, in particular, among the flavonols, and along with kaempferol, myricetin and isorhamnetin, it is recognized as a foreign substance after ingestion in contrast to vitamins. Quercetin occurs mainly linked to sugars with the most common compounds being quercetin-3-O-glucoside or as an aglycone, especially in the plant population. The aim of this review is to present a recent bibliography on the mechanisms of quercetin absorption and metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 123 publications
(165 reference statements)
0
17
0
Order By: Relevance
“…One of the most commonly studied flavonoids is quercetin, which is involved in several plant physiological processes, such as seed germination, photosynthesis and plant growth. Quercetin and its derivatives can present different biological activities due to modifications at significant positions of the quercetin molecule, such as glycosylation or methylation [ 70 ]. Quercetin was shown to protect human brain microvascular endothelial cells from I/R in vitro.…”
Section: Bioactive Compounds With Neuroprotective Effect Against Brai...mentioning
confidence: 99%
“…One of the most commonly studied flavonoids is quercetin, which is involved in several plant physiological processes, such as seed germination, photosynthesis and plant growth. Quercetin and its derivatives can present different biological activities due to modifications at significant positions of the quercetin molecule, such as glycosylation or methylation [ 70 ]. Quercetin was shown to protect human brain microvascular endothelial cells from I/R in vitro.…”
Section: Bioactive Compounds With Neuroprotective Effect Against Brai...mentioning
confidence: 99%
“…Other than being studied as a single treatment, few pre-clinical studies have reported that the combination of quercetin with conventional drugs such as TMZ enhanced the cytotoxic effect in high-grade adult-type diffuse glioma [ 26 , 67 , 68 ]. Numerous pre-clinical studies have also demonstrated that quercetin exhibits selective cytotoxicity in high-grade adult-type diffuse glioma cells against normal cells [ 179 , 180 ]. Several pre-clinical studies also reported that nanoparticles loaded with quercetin, when combined with TMZ, increase the cytotoxicity effects in both drug-sensitive and drug-resistant glioma cells [ 164 ].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Quercetin is a flavonoid and chemically it is a phenyl-substituted chromone composed of a basic skeleton of fifteen carbon atoms, composed of a chromium nucleus formed by the benzo ring A and the heterocyclic ring C, and in the aromatic ring B has a phenyl substitution [ 147 ]. Data have shown that the different substituents in rings A and B are responsible for the pharmacological activities of quercetin [ 148 ].…”
Section: Quercetin As Bioactive Molecule In Cancermentioning
confidence: 99%
“…Although many researchers have attempted to highlight and understand the possible structure-anticancer activity correlation of quercetin, there is a scarcity of data to explain the relationship between chemical structure-cytotoxic and antitumor effect [ 149 ]. As a potential correlation, the hydroxylation pattern of the B ring in the chemical structure of quercetin would be responsible for its antiproliferative effects and inhibition of protein kinase B (AKT) [ 148 , 150 ] (Fig. 3 ).…”
Section: Quercetin As Bioactive Molecule In Cancermentioning
confidence: 99%